Anti-VP6 VHH : an experimental treatment for rotavirus A-associated disease - Maffey, Lucia; Vega, Celina Guadalupe; Miño, Samuel; Garaicoechea, Lorena Laura; Parreño, Viviana (2017)
Species A Rotaviruses (RVA) remain a leading cause of mortality in children under 5 years of age. Current treatment options are limited. We assessed the efficacy of two VP6-specific llama-derived heavy chain antibody fragments (VHH) -2KD1 and 3B2- as an oral prophylactic and therapeutic treatment against RVA-induced diarrhea in a neonatal mouse model inoculated with virulent murine RVA (ECw, G16P[16]I7). Joint therapeutic administration of 2KD1+3B2 (200 μg/dose) successfully reduced diarrhea duration, RVA infection severity and virus shedding in feces. While the same dose of 2KD1 or 3B2 (200 μg) significantly reduced duration of RVA-induced diarrhea, 2KD1 was more effective in diminishing the severity of intestinal infection and RVA shedding in feces, perhaps because 2KD1 presented higher binding affinity for RVA particles than 3B2. Neither prophylactic nor therapeutic administration of the VHH interfered with the host’s humoral immune response against RVA. When 2KD1 (200 μg) was administered after diarrhea development, it also significantly reduced RVA intestinal infection and fecal shedding. Host antibody responses against the oral VHH treatment were not detected, nor did viral escape mutants. Our findings show that oral administration of anti-VP6 VHH constitute, not only an effective prophylactic treatment against RVA-associated diarrhea, but also a safe therapeutic tool against RVA infection, even once diarrhea is present. Anti-VP6 VHH could be used complementary to ongoing vaccination, especially in populations that have shown lower immunization efficacy. These VHH could also be scaled-up to develop pediatric medication or functional food like infant milk formulas that might help treat RVA diarrhea.